The influence of linker substitution on the fluorescence responsive sensing of isostructural coordination polymers: visual turn-on, ratiometric, and turn-off sensing in water. Issue 11 (2nd March 2021) - Chuang, Po-Min; Huang, Yun-Wen; Liu, Yu-Lin; Wu, Jing-Yun
Abstract : Linker substituents show great impacts on the luminescence properties and sensing performances of isostructural coordination polymers, causing turn-on or ratiometric sensing of Fe 3+, Al 3+, and Cr 3+ and turn-off sensing of CrO4 2− and Cr2 O7 2− . Abstract : Four isostructural and isomorphous coordination polymers, {[Zn2 (OH)(NO2 -1, 4-bdc)1.5 (Cz-3, 6-bpy)]·2H2 O} n (1 ), {[Zn2 (OH)(NO2 -1, 4-bdc)1.5 (Cz-Pr-3, 6-bpy)]·0.5H2 O} n (2 ), {[Zn2 (OH)(Br-1, 4-bdc)1.5 (Cz-3, 6-bpy)]·H2 O} n (3 ), and {[Zn2 (OH)(Br-1, 4-bdc)1.5 (Cz-Pr-3, 6-bpy)]·0.5H2 O} n (4 ), where NO2 -1, 4-bdc = 2-nitrobenzene-1, 4-dicarboxylate, Br-1, 4-bdc = 2-bromobenzene-1, 4-dicarboxylate, Cz-3, 6-bpy = 3, 6-bis(pyridin-4-yl)-9 H -carbazole, and Cz-Pr-3, 6-bpy = 3, 6-bis(pyridin-4-yl)-9- n -propyl-9 H -carbazole, have been hydro(solvo)thermally synthesized. Compounds 1–4 have similar two-dimensional layer structures simplified to rhombus grid-like sql nets in topology. Both nitro-substituted 1 and 2 are fluorescence silent, behaving as visual fluorescence turn-on sensors for the detection of Fe 3+, Cr 3+, and Al 3+ in water. Both bromo-substituted 3 and 4 emit strong cyan fluorescence and can be treated as visually ratiometric fluorescent sensors for the detection of Fe 3+, Cr 3+, and Al 3+ and visual fluorescence turn-off sensors for the detection of CrO4 2− and Cr2 O7 2− in water, with high selectivity and sensitivity. The work clearly shows that the substituent (nitro and bromo) on the benzene-1, 4-dicarboxylate linker has a great impact not only on essential luminescence properties but also the fluorescence responsive performances of coordination polymers.